Analisis Kesehatan Bank KBMI 4 Berdasarkan Capital, Asset, Earning, dan Liquidity 2019 – 2023 - Gumilang, Junika Cahya; Sirait, Afni; Sriyono, Sriyono; Zuhrohtun, Zuhrohtun; Marita, Marita (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The influence of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operational Costs and Operational Income (OCOI), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) on the Profitability Ratio (ROA) in Bank Groups based on Core Capital (KBMI) 4 from 2019 to 2023. Methodology/approach: Quantitative research approach was used. The type of data used in this study is secondary data, with a population consisting of the Bank Group Based on Core Capital (KBMI) 4 listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Results/findings: The results of this study indicate that the Capital Adequacy Ratio (CAR) has a positive effect on Return On Assets (ROA), Operating Costs Operating Income (OCOI) has a negative effect on Return On Assets (ROA), Net Interest Margin (NIM) has a positive effect on Return On Assets (ROA), Loan to Deposit Ratio (LDR) has a positive effect on Return On Assets (ROA), on the other hand Non Performing Loan (NPL) has no effect on Return On Assets (R OA). Conclusions: This study finds that CAR, NIM, and LDR positively and significantly affect ROA, whereas BOPO has a negative and significant impact. The NPL showed no significant effect. Overall, 96% of the ROA variation in KBMI 4 banks from 2019 to 2023 is explained by these financial variables, highlighting their strong influence on profitability during economic uncertainty. Limitations: This study is limited to the financial performance ratios used, and the results provided are focused on KBMI 4 banking companies in Indonesia only. Contribution: This study can be used as a literature reference for further research, especially research on the influence of bank health levels on profitability (ROA)  Bank Groups based on Core Capital (KBMI) 4  in Indonesia.